Pengolahan Kupang Desa Balongdowo Sebagai Sumber Belajar Berpendekatan Etnosains di Sekolah Dasar - Ulfa, Armellia; Widodo, Wahono; Istiq'faroh, Nurul (CV. Kurnia Grup, 2025)
The processing of mussels as a local wisdom offers great potential to integrate ethnoscience concepts into the education curriculum. In the realm of ethnoscience, the study of the processing of kupang not only has rich cultural value but also includes various scientific concepts. This research aims to explore how an ethnoscience approach, particularly in the context of processing clams, can be used as a learning resource for elementary school science students. This research falls into the category of descriptive qualitative research. The data collection techniques used in this research to gather in-depth information from various sources include (1) interviews, (2) observations, and (3) documentation studies. The subjects of the research are kupang processors and lontong kupang traders in Balongdowo Village. The research results indicate that the process of processing kupang can be incorporated into the elementary school curriculum as a source of ethnoscience-based learning, which combines cultural values and scientific concepts. This implementation is expected to provide students with insights into the relationship between local practices and scientific principles, as well as to appreciate the local culture. This study highlights that the processing of clams, with all its processes, can be utilized as a medium to instill cultural and scientific values in students from an early age. Thus, it can be concluded that the processing of mussels can be utilized as an ethnoscience-based learning resource to instill cultural values and scientific concepts in students from an early age. This also enriches the elementary school curriculum by utilizing local wisdom, which in turn can enhance students' appreciation of their own culture and provide a deeper understanding of the scientific concepts taught in school. With this approach, education becomes more contextual, meaningful, and engaging for students.